Food fermentation technology: examples of application in Malaysian foods - Ruby, Genevie Eleanor; Abdul Mutalib, Noor Azira; Juhari, Nurul Hanisah; Ungku Zainal Abidin, Ungku Fatimah (Elsevier BV, 2023)
Fermentation is a processing method commonly employed in the food industry and applied worldwide, including in Malaysia. Various types of raw food can be processed by fermentation, such as fish, shrimp, local vegetables, and fruits. Other than prolonging the shelf life of food and increasing its nutritional values, fermentation is the primary method of producing alcoholic beverages. Furthermore, the microorganisms in fermented food contribute to the characteristics of the food and possess beneficial probiotics that are good for human digestion. Nevertheless, the amounts of by-products produced during the process, especially biogenic amines, necessitate management to reduce the harmful effects of histamine intolerance. Recent technology has allowed improvements in fermentation approaches, which enhance the quality of the food and alcoholic beverages produced. Consequently, fermented food is not only a food source but can also be expanded to other fields, such as medicine and agronomy.